Pelatihan dan Pendampingan Penulisan Artikel Ilmiah pada Guru Sekolah Dasar di Kecamatan Air Periukan Kabupaten Seluma Provinsi Bengkulu - Danner Sagala; Supriyono Supriyono; Dodo Sutardi; Prihanani Prihanani (Universitas Prof. Dr. Hazairin, SH, 2019)
Workshop and Mentoring of Scientific Writing on Elementary School Teacher in Air Periukan Subdistrict, Seluma Regency and Bengkulu Province This community service was aimed to help teachers understand the concepts and processes of publicizing scientific articles in scholarly journals. The target of the program was the teachers are able to compile a manuscript and be accompanied until it is ready to be sent to the scholarly journal. The participants were members of the Air Periukan Subdistrict Teacher Working Group in Seluma District, Bengkulu Province. The training was carried out with participatory lecturing and mentoring methods. The results of observations on the implementation of the program through evaluation showed that the teachers had a high interest in being trained to publish scientific articles. However, high interest has not been followed by the number of manuscripts produced. The unfamiliarity of the publication of scientific articles has led to scientific publications becoming a